The sociology of language choice and multilingualism in Zimbabwe: Reflections on language choices by front office personnel in formal workplace discourse. Issue 2 (3rd July 2019) - Chikasha, Jubilee
Abstract : Rural-to-urban migration in Zimbabwe has led to the convergence of different ethnic groups in urban areas. Globalisation has also added to the cultural and linguistic diversity of urban areas. This study investigates the language used by front office personnel in formal workplace discourse. It attempts to identify the language/s that characterise formal workplace discourse, taking into consideration the multilingual nature of the country. Information was collected through observation (both full participant and complete outsider) and semi-structured interview methods. Front office personnel make language choices with the ultimate aim of achieving certain intentions. Thus, language used in a formal workplace context is basically functional in nature. It serves the main purpose of creating, maintaining and attracting new clients to the business. Although the context of the present study is formal workplace discourse, language choice in this context is not only determined by business factors, but also correlates with social norms and values. For the indigenous people of Zimbabwe, the establishment and maintenance of long-lasting relationships is at the very core of cultural existence. It is this need for unity and co-operation that is carried over into the business domain with the ultimate aim of fostering such relationships for commercial benefit.